h - Jiang, Tianzi; Navab, Nassir; Pluim, Josien P. W.; Viergever, Max A.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The three-volume set LNCS 6361, 6362 and 6363 constitutes the refereed proceedings of the 13th International Conference on Medical Image Computing and Computer-Assisted Intervention, MICCAI 2010, held in Beijing, China, in September 2010. Based on rigorous peer reviews, the program committee carefully selected 251 revised papers from 786 submissions for presentation in three volumes. The first volume includes 84 papers organized in topical sections on computer-aided diagnosis, planning and guidance of interventions, image segmentation, image reconstruction and restoration, functional and diffusion-weighted MRI, modeling and simulation, instrument and patient localization and tracking, quantitative image analysis, image registration, computational and interventional cardiology, and diffusion tensor MR imaging and analysis.
Computer-Aided Diagnosis -- Planning and Guidance of Interventions -- Image Segmentation -- Image Reconstruction and Restoration -- Functional and Diffusion-Weighted MRI -- Modeling and Simulation -- Instrument and Patient Localization and Tracking -- Quantitative Image Analysis -- Image Registration -- Computational and Interventional Cardiology -- Diffusion Tensor MR Imaging and Analysis.
Keywords: Computer science; Computer simulation; Computer vision; Computer graphics; Optical pattern recognition; Computer Science; Image Processing and Computer Vision; Pattern Recognition; Computer Graphics; Computer Imaging, Vision, Pattern Recognition and Graphics; User Interfaces and Human Computer Interaction; Simulation and Modeling